An Analysis of Non-Verbal Communication in Susanne Bier’s Movie Bird Box - Firdaus, Firly Febrina; Iskandar, Iskandar; Hasbi, Muh. (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2025)
This research is entitled “An Analysis of of Nonverbal Communication in Susanne Bier’s Movie Bird Box.” This study aims to analyze the types of nonverbal communication in Bird Box movie by Susanne Bier using Fujishin’s theory (2009). The analysis method used refers to the pragmatic approach by considering Yule’s (1996) theory to explore and examine whether the type of nonverbal communication used is appropriate to the situation. The research data were obtained from the extraction of 41 nonverbal communication consisting of body movement (23) extract, paralanguage (12) extract, personal presentation (2) extract, and proxemics (4). The analysis also identified all of the types appropriate to the situation. The findings the film carefully use nonverbal communication as an important tool in conveying messages and working on the overall narrative of the movie. This research is expected to contribute to the understanding of the nonverbal communication especially in the movie.Keywords: Nonverbal Communication, Fujishin, Body Movement, Bird Box